A Dual-Band Non-destructive Dielectric Measurement Sensor Based on Complementary Split-Ring Resonator - Wang, Chen; Liu, Xiaoming; Gan, Lu; Cai, Qing (Frontiers in Physics, 2021)
A dual-band non-destructive dielectric constant sensor based on the complementary split ring resonators is presented. The resonators for both bands use the complementary split ring structure of different sizes. Numerical simulation demonstrates that the resonating frequency and quality factor is dependent on the variation of dielectric constant and loss tangent, making it a potential structure for dielectric measurement. To search for the optimal thickness for measurement, parametric study is conducted and the retrieval expressions are obtained for both bands. The measured results indicate an accuracy of 1.5% in comparison with the data in the literature. In addition, the effect of air gap has been analyzed, showing that it is an important error source and eliminating such effect can improve the measurement accuracy.